Regional social cohesion and fertility rate: Municipality-level analysis in Finland - Soini, Eetu (SocArXiv, 2025)
Declining fertility rates pose a challenge for population structures and socioeconomic sustainability in
developed countries. While many studies find that received social support matters for childbearing on the
individual level, and regional variation in fertility can be considerable, few studies have investigated how
regional social factors relate to fertility rates. In the current study, we used data from 299 municipalities in
Finland to examine how different measures of social cohesion were associated with fertility rates at the
regional level. Data for social indicators were derived from a large national survey (n=100,750), fertility
data were derived from population registries. We applied spatial autoregressive error models to account
for spatial autocorrelation between neighboring municipalities. Regions with higher social support and
more frequent social contacts had higher fertility rates, whereas higher social trust and civic engagement
were associated with lower fertility rates. These associations were stronger for fertility rates among age
groups 20-34. The results suggest that regional social cohesion may be relevant for people’s decisions of
having children.